Mortality Prediction in the Emergency Service Intensive Care Patients with Possible COVID-19: A Retrospective Cross-Sectional Study - Mehmed Ulu; M. Kaya; Y. Tunc; H. Yildirim; A. Halici; A. Coskun (Вестник интенсивной терапии)
INTRODUCTION: Despite the declining clinical importance of Coronavirus Disease 2019 (COVID-19), the virus is still causes mortality in the critically ill patients. This study aims to determine the impact COVID-19 on mortality, evaluate the performance of Acute Physiology and Chronic Health Evaluation-2 Scores (APACHE II), Sequential Organ Failure Assessment Scores (SOFA) and Pneumonia Severity Index (PSI) for mortality prediction in the COVID-19 suspected patients. MATERIALS AND METHODS: This study is a retrospective cross-sectional analysis of patients who were admitted to the pandemic intensive care unit with possible COVID-19. 28-day mortality difference between positive and negative groups was defined as the primary outcome. RESULTS: Of the 397 patients, 111 (28 %) patients had positive polymerase chain reaction (PCR). 75 (67.6 %) patients deceased in the PCR positive group while 163 (57.0 %) patients deceased in the negative group (p > 0,05). The median values of APACHE II, SOFA and PSI scores were significantly higher in the deceased group, for all patients. Cutoff points were determined for APACHE II score at 19 (AUC 0,96, PLR 14, 16, NLR 0,12), SOFA score at 9 (AUC 0,96, PLR 20,23, NLR 0,11) and PSI score at 81 points (AUC 0,91, PLR 7,01, NLR 0,23). The AUCs of PSI was significantly lower from AUC of APACHE II and SOFA score (DeLong Test, p < 0,001). CONCLUSION: There was no statistically significant difference on mortality between positive and negative group.